Determining the deterrence forces composition to prevent the unleashing of enemy aggression based on the principles of system analysis - Koval, Mykhailo; Zahorka, Oleksii; Shchypanskyi, Pavlo; Pavlikovskyi, Anatolii; Koretskyi, Andrii (Eastern-European Journal of Enterprise Technologies, 2023)
The task to determine the composition of forces to deter the enemy from starting aggression, that is, to prevent the hot phase of a military conflict, refers to poorly structured problems in the presence of significant uncertainty. This leads to the application of the methodology of system analysis in solving the task. The set of deterrence forces to defeat the enemy is considered as a complex military system, which is the object of this study. To determine the composition of the enemy's deterrence forces from unleashing armed aggression, this paper reports a devised methodology. The procedure criterion is the effectiveness of deterrence, which is determined by the required ratio of the combat potentials of the aviation of the opposing sides at the end of hostilities. According to the methodology of system analysis, the procedure is based on the formation of options for the composition of enemy forces and the composition of deterrence forces, assessing the effectiveness of their use during hostilities. The effectiveness of the use of forces of opposing parties is assessed by using the method of iterations and methods of queuing theory. Based on the results of the effectiveness assessment, the selection of options for the composition of the deterrence forces is carried out, for which the condition for ensuring the necessary ratio of the combat potentials of the aviation of the parties at the end of hostilities is met. The rational version of the composition of the deterrence forces from those selected is determined by using the taxonomy method, which has made it possible to solve the problem under study. The rational option determines the combat potentials of the components of the deterrence forces, which correspond to the number of units in their composition. The above methodology should be used by state and military authorities when planning the creation of enemy deterrence forces against unleashing armed aggression. The application of the procedure is shown in an illustrative example